Molecular evolution and population genetics of glutamate decarboxylase acid resistance pathway in lactic acid bacteria - Sezgin, Efe; Tekin, Burcu (Frontiers in Genetics, 2023)
Glutamate decarboxylase (GAD) pathway (GDP) is a major acid resistance mechanism enabling microorganisms’ survival in low pH environments. We aimed to study the molecular evolution and population genetics of GDP in Lactic Acid Bacteria (LAB) to understand evolutionary processes shaping adaptation to acidic environments comparing species where the GDP genes are organized in an operon structure (Levilactobacillus brevis) versus lack of an operon structure (Lactiplantibacillus plantarum). Within species molecular population genetic analyses of GDP genes in L. brevis and L. plantarum sampled from diverse fermented food and other environments showed abundant synonymous and nonsynonymous nucleotide diversity, mostly driven by low frequency changes, distributed throughout the coding regions for all genes in both species. GAD genes showed higher level of replacement polymorphism compared to transporter genes (gadC and YjeM) for both species, and GAD genes that are outside of an operon structure showed even higher level of replacement polymorphism. Population genetic tests suggest negative selection against replacement changes in all genes. Molecular structure and amino acid characteristics analyses showed that in none of the GDP genes replacement changes alter 3D structure or charge distribution supporting negative selection against non-conservative amino acid changes. Phylogenetic and between species divergence analyses suggested adaptive protein evolution on GDP genes comparing phylogenetically distant species, but conservative evolution comparing closely related species. GDP genes within an operon structure showed slower molecular evolution and higher conservation. All GAD and transporter genes showed high codon usage bias in examined LAB species suggesting high expression and utilization of acid resistance genes. Substantial discordances between species, GAD, and transporter gene tree topologies were observed suggesting molecular evolution of GDP genes do not follow speciation events. Distribution of operon structure on the species tree suggested multiple independent gain or loss of operon structure in LABs. In conclusion, GDP genes in LABs exhibit a dynamic molecular evolutionary history shaped by gene loss, gene transfer, negative and positive selection to maintain its active role in acid resistance mechanism, and enable organisms to thrive in acidic environments.